Cuidado transcultural de enfermagem à mulher imigrante no ciclo gravídico-puerpural em um município de fronteira - Vaz, Maryelen Dornelles Zarth (2023)
The puerperal pregnancy cycle is a unique period of intense transformation and women from different cultures can experience this period differently. Values, beliefs and habits are influenced by culture and can have an impact on women's experience and health during this period, as well as on the care provided. Driven by the process of globalization, the large influx of immigrants has influenced health professionals' ways of caring and the organization of health services. In border regions, the growing demand from a culturally diverse population is a reality in health services. Considering the transcultural care proposed by Madeleine Leininger and the multiculturalism of the research setting, the aim of the study was to understand the experience and nursing care of immigrant women in the pregnancypuerperal cycle. This is a qualitative and exploratory study, based on Madeleine Leininger's Theory of Diversity and Universality of Cultural Care. The research was conducted in Foz do Iguaçu, a municipality in a triple border with unique cultural diversity. Data were collected through in-depth interviews, face-to-face and using Google Meet software, with eight immigrant puerperae from different cultures and 18 nurses working in primary and hospital care, between February and September 2022. The interpretation of meanings proposed by Romeu Gomes was used to analyze the data. The results were presented in two articles: Cultural care for immigrant women in the pregnancy-puerperal cycle and Pregnancy and childbirth in an immigrant situation: experiences, care and vulnerabilities. The experiences shared by immigrants from different cultures point to socio-economic difficulties and access to work, lack of family and social support, cultural differences and the health system in Brazil, revealing the vulnerabilities that immigrant women experience in the pregnancy-puerperal cycle. Cultural differences were more evident for women who immigrated from more distant countries. The experiences still point to the satisfactory and quality care received by health service professionals, as well as the appreciation of professional knowledge, with an emphasis on the multi-professional team. In the provision of care, barriers of access and language were identified, as well as a lack of planning of the demand for care, resulting in fragmented and discontinuous care. Nurses recognize that cultural aspects can facilitate or hinder the provision of care and that welcoming, preserving, negotiating and restructuring care that is legitimized by cultural care facilitates care for immigrant women in the pregnancy-puerperal cycle. Strengthening public policies for the immigrant population and building protocols and educational actions focused on cultural competence are necessary ways to achieve culturally congruent care and ensure that all women have access to quality care, regardless of their cultural origin.